Lechon a metaphor for the ideal familial relationship - De Roca, Tammy B.
The concept of the "ideal" is reinforced by appearances. This is the gist of this thesis undertaking. The thesis proponent defines "ideal" as "acceptable" or "conceivable", hat which is pleasing to society. Wide as it is, her articulation of the concept of the ideal is focused on her personal relationship wit her nuclear family vis a vis wit the nuclear family's relationship with the public. Years of cohabitation; the quality of familial relationship she has established with its members; and her inevitable immersion into the family's business had resulted to a very personal point of view regarding the concept of the ideal: that appearances help create the nyth of the ideal and at the sane time, promotes deception. The matter a person projects himself/herself to the public is, in the eyes of the proponent, paramount to how the public would create an ideal image of that person. As appearances fuel an ideal, they also solidify the perceived status and value of being ideal. Having an acceptable or conceivable appearance places one on a higher pedestal. Such perception is manifested in the different societal hierarchy, especially in families. For her undergraduate thesis, the proponent draws parallelism between the outward projection of her familial relationship to the public and the socioeconomic status of said family seen as ideal. Her thesis attempts to tackle, through an artwork, the unseen truth underneath the perceived ideal created by acceptable appearances perpetuated by the family. The visual articulation, however, is done metaphorically. She chooses to embody her concern in a sculptural form that, in her eyes, symbolically and appropriately represent her nuclear family and its perceived public image of being ideal. The roasted pig, or commonly called lechon, is the local delicacy that made the family a leader in the lechon industry. She has observed that much of the success of the family's business depends largely on the high quality of the product; the public loves a beautifully roasted pig both in looks and tastes. And to stay on top, the family has to maintain such high standard. Similarly, the same standard is required of the members of the family. One can say that the lechon becomes the yardstick. For her thesis, the proponent satirizes the lechon in an attempt to metaphorically reveal the unseen and unsavory truth behind the ideal of an image created y the success of the family's business venture, as well as the physical and emotional strains it brought to her relationship with the core family and its members. She figuratively casts light on the sculptural forms'-ceramic sculptures in the form of a lechon - myriad natural mishaps (imperfections) as visual interpretation of her personal take on a failed familial relationship hiding within an "ideal family".